Chemical Productions and Immunological Assessments of Cancer Vaccines According to Α-Galactosylceramide and Ganglioside Antigen - Noor Abd Al-Zahra Ali; Aysar Ahmed Ali; Khawla Abdulkader Ossama (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
iNKT cells, sometimes known as the immune system's